Harmonizing neuropathic pain research: outcomes of the London consensus meeting on peripheral tissue studies - Villa, Sara; Aasvang, Eske K.; Attal, Nadine; Baron, Ralf; Bourinet, Emmanuel; Calvo, Margarita; Finnerup, Nanna B.; Galosi, Eleonora; Hockley, James R. F.; Karlsson, Pall; Kemp, Harriet; Körner, Jannis; et al. (Pain, 2025)
Neuropathic pain remains difficult to treat, with drug development hampered by an incomplete understanding of the pathogenesis of the condition, as well as a lack of biomarkers. The problem is compounded by the scarcity of relevant human peripheral tissues, including skin, nerves, and dorsal root ganglia. Efforts to obtain such samples are accelerating, increasing the need for standardisation across laboratories. In this white paper, we report on a consensus meeting attended by neuropathic pain experts, designed to accelerate protocol alignment and harmonization of studies involving relevant peripheral tissues. The meeting was held in London in March 2024 and attended by 28 networking partners, including industry and patient representatives. We achieved consensus on minimal recommended phenotyping, harmonised wet laboratory protocols, statistical design, reporting, and data sharing. Here, we also share a variety of relevant standard operating procedures as supplementary protocols. We envision that our recommendations will help unify human tissue research in the field and accelerate our understanding of how abnormal interactions between sensory neurons and their local peripheral environment contribute towards neuropathic pain.
Gesehen am 26.05.2025